Recent Advances in Bio‐Compatible Oxygen Singlet Generation and Its Tumor Treatment. Issue 1 (12th November 2021) - Jin, Zheng Yang; Fatima, Hira; Zhang, Yue; Shao, Zongping; Chen, Xiang Jian
Abstract: Light‐dependent singlet oxygen ( 1 O2 ) produced in photodynamic therapy (PDT), is a biologically compatible reactive oxygen species showing the potential to kill tumor cells with fewer side effects on nearby normal healthy cells. The development of a high 1 O2 generating photosensitizer is a particularly demanding research areas. Based on Jablonski's diagram, the photophysical factors influencing the generation of 1 O2 are intersystem crossing, triplet quantum yield and life, and the singlet‐triplet energy gap. Moreover, nanocarriers are also an emerging research topic with enhanced/localized delivery of photosensitizers to improve the dosage of light and enriched production of 1 O2 . In this review, the production principle of 1 O2 in PDT and its killing mechanism with respect to tumor cells are reviewed. In addition, the progress of PDT has been supplemented in clinical applications in recent years and the emergent preclinical tactics for prospective solutions to these challenges are discussed to improve the effectiveness and usefulness of these procedures. Moreover, the remaining research gaps and future work is outlined. This review is anticipated to heighten the research for developing new strategies for modulating the photophysical properties and improved the delivery of photosensitizers. Abstract : Enhanced tumor treatment requires the modulation of photophysical properties of photosensitizers (PSs) including intersystem crossing, triplet quantum yield and life, and the singlet‐triplet energy gap to achieve high 1 O2 generation. In addition advancement in nanocarriers is also beneficial in improving the PSs delivery at localized targets and enhanced light dosage conveyance.